Classroom Management as a Control Strategy for Promoting Quality Education in Nigeria - Azubuike, P. Idu (Mediterranean Journal of Social Sciences, 2012)
Classroom management has been viewed as a control strategy for effective instructional and curricularactivities towards ensuring quality and relevant education at all levels. Consequently, there is need toensure a good and sound classroom environment for effective delivery of the teaching and learningprocess. The paper underscored the need for revitalizing classroom management and therefore calls on theteacher skills in ensuring effective discharge of instructional responsibilities. An overview of classroommanagement in the school were highlighted. Finally, the paper highlights key principle or factors ofimproving the learning environment so as to bring about the desired qualitative education in Nigeria.